1983
DOI: 10.1139/f83-085
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of a Swimbladder Nematode, Cystidicola stigmatura (Leidy), and Evidence of its Decline in the Great Lakes

Abstract: Cystidicola stigmatura (Leidy, 1886) Ward and Magath, 1917 is considered a valid species after examination of specimens from Leidy's collection. Cystidicola cristivomeri White, 1941 is considered a synonym of C. stigmatura. Cystidicola stigmatura is distinguished from the only other species in the genus, namely C. farionis Fischer, 1798, by the presence of lateral lobes on the eggs rather than filaments. A neotype of F. stigmatura is designated. Cystidicola stigmatura has not been found in fishes in the Great … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…(Hoffman, 1999). The presence of filaments that were either lateral or polar in arrangement on eggs collected from the nematodes suggested that the nematodes collected in this study were Cystidicola farionis Fischer 1798, while the absence of lateral lobes on the eggs excluded C. stigmatura as the agent of infection (Lankester and Smith, 1980;Black, 1983;Dextrase, 1987;Miscampbell et al, 2004;Hoffman, 1999). Additional confirmation of C. farionis as the swimbladder nematode infecting lake whitefish in northern lakes Huron and Michigan came from examination of the nematode mouth parts, which showed the absence of a prominent lip projection in the pseudolabia.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…(Hoffman, 1999). The presence of filaments that were either lateral or polar in arrangement on eggs collected from the nematodes suggested that the nematodes collected in this study were Cystidicola farionis Fischer 1798, while the absence of lateral lobes on the eggs excluded C. stigmatura as the agent of infection (Lankester and Smith, 1980;Black, 1983;Dextrase, 1987;Miscampbell et al, 2004;Hoffman, 1999). Additional confirmation of C. farionis as the swimbladder nematode infecting lake whitefish in northern lakes Huron and Michigan came from examination of the nematode mouth parts, which showed the absence of a prominent lip projection in the pseudolabia.…”
Section: Discussionmentioning
confidence: 74%
“…Nematodes were cleared in a mixture of glycerol and 70% ethanol (1:1) at room temperature and examined microscopically. Mature and larval-stage nematodes were identified using the dichotomous keys of Ko and Anderson (1969), Smith and Lankester (1979), Lankester and Smith (1980), Black and Lankester (1980), Black (1983), Dextrase (1987), Hoffman (1999), and Miscampbell et al (2004. Total numbers of nematodes, as well as maturation stage and sex of mature nematodes, were recorded for each lake whitefish.…”
Section: Parasite Identification and Swimbladder Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, a fishery can fish out parasites if a stock is fished to a density below the host density threshold for transmission (Dobson and May 1987). For example, fishing apparently lead to the extinction of a swim bladder nematode ( Cystidicola stigmatura , Thelaziidae) from lake trout ( Salvelinus namaycush , Salmonidae) in the Great Lakes (Black 1983) and significantly reduced the prevalence of a tapeworm ( Triaenophorus crassus , Triaenophoridae) in common whitefish ( Coregonus lavaretus , Salmonidae) (Amundsen and Kristoffersen 1990). The significant decline in the normalized reports of disease in marine fish (Ward and Lafferty 2004) was based almost entirely on data from commercially fished species, and this suggests the hypothesis that exploitation has reduced diseases in fishes by making transmission more difficult (Lafferty et al.…”
Section: Discussionmentioning
confidence: 99%
“… References: 1 Black 1983, 1985 ; 2 Dobson & May 1987; 3 Amundsen & Kristoffersen 1990 ; 4 Lafferty & Holt 2003; 5 Ward & Lafferty 2004 ; 6 McCallum et al. 2005; 7 Stokesbury et al.…”
Section: Synthesismentioning
confidence: 99%